2023
DOI: 10.1111/bph.16262
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac side effects of RNA‐based SARS‐CoV‐2 vaccines: Hidden cardiotoxic effects of mRNA‐1273 and BNT162b2 on ventricular myocyte function and structure

Rolf Schreckenberg,
Nadine Woitasky,
Nadja Itani
et al.

Abstract: Background and PurposeTo protect against SARS‐CoV‐2 infection, the first mRNA‐based vaccines, Spikevax (mRNA‐1273, Moderna) and Comirnaty (BNT162b2, Pfizer/Biontech), were approved in 2020. The structure and assembly of the immunogen – in both cases, the SARS‐CoV‐2 spike (S) glycoprotein – are determined by a messenger RNA sequence that is translated by endogenous ribosomes. Cardiac side effects, which for the most part can be classified by their clinical symptoms as myo‐ and/or pericarditis, can be caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Baumeier et al found Spike protein and no nucleocapsid in the myocardium of 15 individuals with COVID-19 vaccine-induced myocarditis [27]. Schrekenberg et al found that in isolated cardiomyocytes, both mRNA-1273 and BNT162b2 induce cardiac dysfunctions that are seen in cardiomyopathies [28]. Krauson et al identified the presence of COVID-19 vaccine mRNA in the hearts of individuals who died within 30 days after vaccination, along with histologically confirmed myocardial injury [29].…”
Section: Discussionmentioning
confidence: 99%
“…Baumeier et al found Spike protein and no nucleocapsid in the myocardium of 15 individuals with COVID-19 vaccine-induced myocarditis [27]. Schrekenberg et al found that in isolated cardiomyocytes, both mRNA-1273 and BNT162b2 induce cardiac dysfunctions that are seen in cardiomyopathies [28]. Krauson et al identified the presence of COVID-19 vaccine mRNA in the hearts of individuals who died within 30 days after vaccination, along with histologically confirmed myocardial injury [29].…”
Section: Discussionmentioning
confidence: 99%
“…The improper reporting and insufficient scrutiny by the VRBPAC may have ultimately enabled Pfizer to manipulate the trial results and obscure the cardiac death signal. Recent in vivo animal studies demonstrate that “in isolated cardiomyocytes, both mRNA-1273 and BNT162b2 induce specific dysfunctions that correlate pathophysiologically to cardiomyopathy” [ 80 ]. In principle, then, cardiomyocytes cannot be excluded from the biodistribution of the LNP-mRNA, and every new mRNA product has the potential to cause life-threatening heart problems, including cardiomyopathy and cardiac arrest.…”
Section: Reviewmentioning
confidence: 99%
“…Vaccine mRNA was isolated in the human heart at autopsy out to 30 days [ 195 ]. Direct cardiotoxicity of the Pfizer and Moderna mRNA vaccines on rat cardiomyocytes has been documented 48 hours after the injection [ 80 ]. S-protein and active inflammation were observed upon biopsy in young individuals hospitalized with COVID-19 vaccine myocarditis [ 203 ].…”
Section: Reviewmentioning
confidence: 99%
“…In a study of isolated rat cardiomyocytes, both messenger ribunucleic acid (mRNA)-1273 (Moderna) and BNT162b2 led to the expression of the spike protein in cardiomyocytes 48 hours after vaccination, mRNA-1273 induced arrhythmic and completely irregular contractions associated with irregular and localized calcium transients, suggesting dysfunction of the cardiac ryanodine receptor (RyR2), and BNT162b2 increased cardiomyocyte contractility via increased protein kinase-A (PKA) activity on the cellular level. 3 A third limitation is that autonomic function was not included in the analysis. Because systolic function depends on the balance between sympathetic and parasympathetic drive, we should know how the level of sympathetic activation was measured and included in the assessment.…”
Section: Dear Editormentioning
confidence: 99%